Epidemiology of Malaria in Amritsar District of India - Vishal Gupta; Mridula Mittal; Vishal Sharma (Oman Medical Journal, 2014)
Objective: Malaria is today one of the major causes of human suffering, both in terms of increasing morbidity/mortality and stunting intellectual/ economic growth. In a developing country like India, it has devastating socioeconomic consequences. The present study was therefore carried out to study the epidemiology of malaria in Amritsar district.